Association of Mild Thyroid Dysfunction and Adverse Prognosis Among Chinese Patients With Acute ST Segment Elevation Myocardial Infarction - Li, Mei-Fang; Wei, Ze-Tao; Li, Shuai; Feng, Qi-Ming; Li, Jing-Bo (Frontiers in Endocrinology, 2022)
Aims: Thyroid hormones widely affect the cardiovascular system, but the effects of mild thyroid dysfunction on the clinical prognosis of patients with acute ST segment elevation myocardial infarction (STEMI) remains unclear. Our aims were to analyze the relations between mild thyroid dysfunction at admission and clinical outcomes in Chinese patients with STEMI. Methods: 1176 STEMI patients with available data of thyroid function and follow-up were analyzed, including 348 patients with mild thyroid dysfunction [subclinical hypothyroidism (SCH) (n=81), hyperthyroidism (SHyper) (n=51) and low triiodothyronine syndrome (LT3S) (n=216)] and 828 patients with euthyroid function. During a median 4.4-year follow-up, in-hospital mortality, cardiac and all-cause mortalities were subsequently compared among the four groups. Results: Compared with the euthyroid group, STEMI patients in the SHyper and LT3S groups faced obviously increased risks of in-hospital death [odds ratio (OR): 5.007, 95% confidence interval (CI): 1.246 to 20.124, p = 0.023 and OR: 2.491, 95% CI: 1.054 to 5.887, p = 0.037, respectively) even after adjustment for various confounding factors. During a median 4.4-year follow-up, STEMI patients with LT3S at baseline had higher cardiovascular mortality [hazard ratio (HR): 1.880, 95% CI: 1.178 to 2.998, p = 0.008] and all-cause mortality [hazard ratio (HR): 1.647, 95% CI: 1.072 to 2.531, p = 0.023] than those with euthyroid at baseline, whereas no significantly increased mortality were found for STEMI patients with SCH and SHyper at baseline. Conclusions: STEMI patients with SHyper at admission had increased risk of in-hospital mortality, and STEMI patients with LT3S at baseline had worse prognosis and higher incidences of in-hospital mortality, cardiovascular and all-cause deaths compared with euthyroid patients.